Experiences of employment among young people with juvenile idiopathic arthritis: a qualitative study. Issue 16 (31st July 2018) - Hanson, Helen; Hart, Ruth I.; Thompson, Ben; McDonagh, Janet E.; Tattersall, Rachel; Jordan, Alison; Foster, Helen E.
Abstract: Purpose: This study explored expectations and experiences of employment among young people with juvenile idiopathic arthritis and the role of health professionals in promoting positive employment outcomes. Methods: Semistructured interviews ( n  = 13) and three focus groups ( n  = 9, n  = 4, n  = 3) were conducted with young people (16–25 y) and adults (26–31 y) with juvenile idiopathic arthritis and semistructured interviews ( n  = 9) were conducted with health professionals. Transcripts were analyzed thematically. Results: Young people with juvenile idiopathic arthritis have concerns about employers' attitudes toward employees with long-term health conditions and lack knowledge of antidiscrimination legislation. Young people not in education, employment or training identify arthritis as a key barrier. Challenges associated with arthritis (e.g., pain, psychological distress) may not be visible to employers. Decisions about disclosing arthritis are challenging and cause anxiety. Young people associate good disease management and access to flexible and convenient care with their capacity to succeed in employment. Psychosocial and vocational interventions have benefited some young people but are not routinely available. Conclusions: Low expectations of employers may affect young people's decisions about disclosure and seeking appropriate support in the work place. Health professionals can equip young people with knowledge and skills to negotiate appropriate support, through signposting to antidiscrimination information and offering practice of transferable skills such as disclosure in consultations. Implications for rehabilitation: Young people with juvenile idiopathic arthritis encounter challenges with regard to employment; many lack the knowledge and skills to negotiate appropriate support from employers. Rehabilitation professionals could play a more substantial role in equipping them with relevant knowledge and skills by signposting to antidiscrimination information and nurturing transferable skills, such as disclosure, in consultations. Potentially helpful interventions, such as group activities or assessment by a psychologist, have benefited some but need more evaluative scrutiny with respect to employment outcomes.